The Penal Code of 1968 - A New Stage in the Development of Bulgarian Criminal Law - Radeva, Neli (Research Papers, 2020)
This study is dedicated to the 50th anniversary of the adoption of the Penal Code in 1968 and represents a new stage in the development of our criminal law. It completes criminal codification. It is based on the basic principles of the penal policy of the Bulgarian socialist state. A number of new positions and institutes have been affected. Its education would give an knowledge of the reforms that have been made and it is a valuable source for future legislative changes.